Using Film to Increase Motivation for Speaking in English Course Classroom - Siska, Siska (TELL - US JOURNAL, 2015)
Motivation is very essential aspect that can help the students to speak English as the foreign language. As the practitioner, the researcher becomes  aware about the important of motivation so that she did the research by applying film as teaching media and this research aims  to investigate whether the students’ motivation to speak  could be increased by using this media. The type of the research is action research that was done in one cycle for 10 meetings in English course classroom that had 10 participants of senior high school students. All of the empirical data were collected through observation, field note and interview and then those data were described and interpreted by the researcher to find out the result of the research. Findings show that most of the students accept and agree on learning by using film and their high motivation could be seen from their desire and action in the discussion activity which is related to the film. Here, the students became active to give their opinion and point of view about the film and they could speak more fluently than before. It is hoped that the findings of this research create the new spirit of the teachers who teach formal or non-formal schools to apply or use film as teaching media in English classroom.